Determinants of turnover intention: The case of public servants in Vietnam - Phuong V. Nguyen; Nga Le; Hoa Trieu; Tien Huynh; Hoa Quynh Tran (Problems and Perspectives in Management, 2022)
Turnover intention is an essential issue for every organization as retaining experienced and knowledgeable employees is an essential factor contributing to an organization’s competitive advantage and sustainable growth. Governmental and non-profit organizations, in particular, need to develop measures for reducing the increasing rate of turnover among federal officials. This study examines the factors influencing intentions to leave among civil servants in the public administration sector. Therefore, an online survey was undertaken to collect data from the targeted respondents, who are employees and managers working in governmental organizations in Vietnam. By using the convenience sampling method, a total of 300 responses were obtained. Men made up 53.3% of the participants, while women made up the remainder. Nearly 60% of the participants work for governmental and political organizations, and the rest work for state unions. The collected data were then processed via AMOS software and analyzed using the Structural Equation Modeling approach. The results indicate that job satisfaction strongly affects employees’ turnover intentions, with a path coefficient of 0.352 and a p-value less than 0.001. In addition, perceived organizational support has a significant positive relationship with organizational commitment, evidenced by the path coefficient of 0.315 and p-value less than 0.001. Overall, the results suggest that organizations are more likely to retain qualified and committed employees when they attempt to develop appropriate training programs and an incentive reward system.